Islet amyloid with macrophage migration correlates with augmented β-cell deficits in type 2 diabetic patients. (September 2014) - Kamata, Kosuke; Mizukami, Hiroki; Inaba, Wataru; Tsuboi, Kentaro; Tateishi, Yoshinori; Yoshida, Taro; Yagihashi, Soroku
Abstract Aims: Islet amyloid is a hallmark in type 2 diabetic subjects, but its implication in clinical features and development of islet pathology is still unclear. Methods: From 118 autopsy cases with type 2 diabetes, 26 cases with islet amyloid deposition (DA+) were selected. Twenty diabetic subjects without obvious amyloid deposition (DA−) matched for the age and diabetes duration and 20 non-diabetic subjects (ND) served for comparison. We examined the severity of amyloid deposition and its relationships with population of endocrine cells, expression of cell damage markers or macrophage infiltration. Correlation of clinical profile with islet pathology was also sought on the subset of the investigated patients. Results: β-Cell volume density was nearly 40% less in DA+ and 20% less in DA− when compared to ND. Severity of amyloid deposition correlated with reduced volume densities of β-cell and α-cell, and increased body mass index (BMI), but not with duration of diabetes, age or HbA1c. Amyloid-rich islets contained an increased number of macrophages mixed with β-cells with oxidative stress-related DNA damage, characterized by γH2AX expression, and suppressed (pro)insulin mRNA expression. Conclusions: In Japanese type 2 diabetic patients, islet amyloid was more common with severe β-cell loss and high BMI, associated with macrophage infiltration.